Merdeka Belajar Kampus Merdeka (MBKM): Ideological Power Relationship - Rachmat Rachmat; Andi Ihsan (International Conference on Science, Education, and Technology, 2022)
Talking about education, the position is like being in a wide and deep sea. Therefore, education is always changing from time to time whose goal will be to swim to land or dive into the deep sea. Based on this, the author presents this paper with the aim of reviewing the education policy era of Minister Nadiem Makarim in the educational ideology agenda. MBKM through its 4 main policies seems to be systematically dehumanizing through a systematic way of working, which puts students into the screws in the framework of industrial development .